Association between childhood maltreatment and the prevalence and complexity of multimorbidity: A cross-sectional analysis of 157, 357 UK Biobank participants. (31st July 2020) - Hanlon, Peter; McCallum, Marianne; Jani, Bhautesh Dinesh; McQueenie, Ross; Lee, Duncan; Mair, Frances S
Background: Child maltreatment is associated with long-term conditions (LTCs) in adulthood. Its relationship to multimorbidity (≥2 LTCs) is less clear. We explore the relationship between child maltreatment, multimorbidity and factors complicating management. Methods: Cross-sectional analysis of 157, 357 UK Biobank participants. Experience of four maltreatment types (physical/sexual/emotional/neglect) was identified. We explored the relationship between type, number and frequency of maltreatment and LTC count (0, 1, 2, 3, ≥4) using multinomial logistic regression. Binary logistic regression assessed the relationship between maltreatment and self-rated health, loneliness, social isolation, frailty and widespread pain in those with multimorbidity, adjusting for sociodemographics and lifestyle factors. Results: 52, 675 participants (33%) experienced ≥1 type of maltreatment; 983 (0.6%) experienced all four. Type, frequency and number of types of maltreatment were associated with higher LTC count. People experiencing four types of maltreatment were 5 times as likely to have a LTC count of ≥4 as those experiencing none (odds ratio (OR): 5.16; 99% confidence interval (CI): 3.77-7.07). Greater number of types of maltreatment was associated with higher prevalence of combined physical/mental health LTCs (OR: 2.99; 99% CI: 2.54–3.51 for four types of maltreatment). Compared to people who reported no maltreatment, people experiencing all four types of maltreatment were more likely to have poor self-rated health (OR: 3.56; 99% CI: 2.58–4.90), loneliness (OR: 3.16; 99% CI: 2.17–4.60), social isolation (OR: 1.45; 99% CI: 1.03–2.05), widespread pain (OR: 3.19; 99% CI: 1.87–5.44) and frailty (OR: 3.21; 99% CI: 2.04–5.05). Conclusion: Peoplewith a history of maltreatment have higher LTC counts and potentially more complicated management needs reinforcing calls for early intervention.